Electroacupuncture reduces chronic itch via cannabinoid CB1 receptors in the ventrolateral periaqueductal gray - Ge, Wen-Qiang; Zhan-Mu, Ou-Yang; Chen, Chao; Zhang, Hong; Wang, Xiao-Yu; Liu, Xin; Li, Li; Lan, Yu-Ye; Li, Chen-Nan; Sun, Jia-Can; Shi, Run-Lin; Dou, Zi-Yue; et al. (Frontiers in Pharmacology, 2022)
Chronic itch severely reduces the quality of life of patients. Electroacupuncture (EA) is widely used to treat chronic itch. However, the underlying mechanism of this therapeutic action of EA is largely unknown. Cannabinoid CB1 receptors in the ventrolateral periaqueductal gray (vlPAG) mediate the analgesic effect of EA. Using a dry skin-induced itch model in mice, we determined whether EA treatment reduces chronic itch via CB1 receptors in the vlPAG. We showed that the optimal effect of EA inhibiting chronic itch was achieved at the high frequency and high intensity (100 Hz and 3 mA) at "Quchi" (LI11) and "Hegu" (LI14) acupoint, which are located in the same spinal cord segment as the cervical skin lesions. EA reversed the increased expression of CB1 receptors in the vlPAG and decreased the concentration of 5-hydroxytryptamine (5-HT) in the medulla oblongata and the expression of gastrin-releasing peptide receptors (GRPR) in the cervical spinal cord. Furthermore, knockout of CB1 receptors on GABAergic neurons in the vlPAG attenuated scratching behavior and the 5-HT concentration in the medulla oblongata. In contrast, knockout of CB1 receptors on glutamatergic neurons in the vlPAG blocked the antipruritic effects of EA and the inhibitory effect of EA on the 5-HT concentration in the medulla oblongata. Our findings suggest that EA treatment reduces chronic itch by activation of CB1 receptors on glutamatergic neurons and inhibition of CB1 receptors on GABAergic neurons in vlPAG, thereby inhibiting the 5-HT release from the medulla oblongata to GRPR-expressing neurons in the spinal cord. Our findings suggest that EA attenuates chronic itch via activating CB1 receptors expressed on glutamatergic neurons and downregulating CB1 receptors on GABAergic neurons in the vlPAG, leading to the reduction in 5-HT release in the rostroventral medulla (RVM) and GRPR signaling in the spinal cord. Our study not only advances our understanding of the mechanisms of the therapeutic effect of EA on chronic itch but also guide the selection of optimal parameters and acupoints of EA for treating chronic itch.